Effects of Smoking Cessation with Nicotine Replacement Therapy on Vascular Endothelial Function, Arterial Stiffness, and Inflammation Response in Healthy Smokers. (September 2019) - Xue, Chao; Chen, Qi Zhi; Bian, Ling; Yin, Zhao Fang; Xu, Zuo Jun; Zhang, A Lian; Xie, Yu Shui; Zhang, Hui Li; Du, Run; Wang, Chang Qian
The effects of nicotine replacement therapy (NRT)-aided smoking cessation on vascular function are not fully clarified. We investigated 100 healthy smokers who were motivated to quit and received NRT for a 3-month period. Vascular endothelial function (measured by reactive hyperemia-peripheral arterial tonometry [RH-PAT]), arterial stiffness (measured by augmentation index [AI] and brachial-ankle pulse wave velocity [baPWV]), and systemic inflammation markers (including serum soluble intercellular adhesion molecule-1 [sICAM-1] and interleukin-1β [IL-1β]) were assessed at baseline and 3 and 12 months of follow-up. After 3 months of intervention, endothelial function, arterial stiffness, and inflammatory markers significantly improved (RH-PAT increased, AI and baPWV decreased, sICAM-1 and IL-1β decreased, all P < .05) for the participants who abstained from smoking completely, but for those who did not abstained completely, RH-PAT, AI, baPWV, and IL-1β remained unchanged. At 12 months follow-up, endothelial function (RH-PAT), arterial stiffness (AI and baPWV), and inflammatory markers (sICAM-1 and IL-1β) were further improved in participants who abstained from smoking ( P < .001), while the above parameters deteriorated in continued smokers ( P < .05). In conclusion, vascular dysfunction can be reversible after NRT-aided smoking cessation in healthy smokers and vascular function could be further damaged if they continue smoking.